The Degree of Availability of Six Sigma Application Requirements at Taif University from the Point of View of Faculty Members - Mansour Maqableh (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
The study aims to identify the degree of availability of the requirements for the application of Six Sigma at Taif University from the point of view of the faculty members. To achieve the objectives of the study, the descriptive survey method was used. The study tool consisted of (42) items distributed over five domains applied to a sample of (225) faculty members. The results of the study showed that the degree of availability of the requirements for the application of Six Sigma at Taif University from the point of view of faculty members was moderate.  Further, the results showed that there were no statistically significant differences at the significance level (α = 0.05) due to the effect of gender and academic rank, and there were statistically significant differences at (α = 0.05) due to the effect of the college, and the differences came in favor of the humanities colleges, and there were statistically significant differences at (α = 0.05) due to the effect of experience among those with more than (10) years of experience and less than (5) years, the differences came in favor of those with more than (10) years of experience. Considering the results of the study, the researcher recommends the necessity of disseminating the concept of Six Sigma and the organizational culture among university employees, working to provide qualified trainers and experts, and holding courses for faculty members in the field of Six Sigma.